Traffic Congestion Analysis and Ten-Year Traffic Condition Forecasting Using the PKJI 2023 Method: Case Study : Siliwangi Cicurug-Benda Road - Hidayat, Muhammad; Permadi, Dio D; Oktriadi, Rivaldi Tresna (Jurnal Teknik Sipil MACCA, 2026)
Sukabumi Regency in West Java has experienced rapid development, increasing the need for efficient transportation infrastructure to support mobility and goods distribution. One strategic corridor is the Siliwangi Cicurug–Benda Highway section STA 30+000–STA 31+000, which often experiences congestion, particularly during operational disruptions of major infrastructure such as Bocimi Toll Road Section 2. This study analyzes road performance using the PKJI 2023 method before and after the toll road resumed operation. Results show that traffic volume decreased from 4,290 vehicles/hour during toll disruption to 3,788 vehicles/hour after reopening. Road capacity was recorded at 3,352.3 smp/hour, while the degree of saturation (DJ) improved from 0.85 to 0.70, indicating better traffic performance. Traffic growth projections for the next decade show vehicle volume increasing from 2,480.03 smp/hour in 2026 to 3,708.76 smp/hour in 2035, with DJ exceeding the recommended limit of 0.85 starting in 2029 and reaching 1.11 in 2035. Road widening is proposed as a solution, increasing capacity to 4,216.40 smp/hour and reducing DJ from 0.74 to 0.59, thus improving performance. However, projections indicate DJ may again exceed acceptable limits by 2035, suggesting the need for additional long-term traffic management strategies to maintain optimal road performance.